Effects of 15-Days −6° Head-Down Bed Rest on the Attention Bias of Threatening Stimulus - Jiang, Shan; Qian, YI-Ming; Jiang, Yuan; Cao, Zi-Qin; Xin, Bing-Mu; Wang, Ying-Chun; Wu, Bin (Frontiers in Psychology, 2022)
Previous researchers have found that head-down bed rest (HDBR) will affect the emotional state of individuals, and negative emotions such as anxiety are closely related to attention bias. The present study adopted the dot-probe task to evaluate the effects of 15-days of −6° HDBR on the attention bias of threatening stimulus in 17 young men, which was completed before (Pre-HDBR), during (HDBR-1, HDBR-8, HDBR-15), after (Post-HDBR) the bed rest. In addition, self-report inventories (State Anxiety Inventory, SAI; Positive Affect and Negative Affect Scale, PANAS) were conducted to record emotional changes. The results showed that the participants’ negative affect scores on HDBR-8 were significantly lower than the HDBR-1 in PANAS while there was no significant difference on positive affect scores and anxiety scores in SAI. And the results showed that at the Pre-HDBR, HDBT-1, HDBR-15, Post-HDBR, the response speed to threatening stimulus was faster than neutral stimulus, but no statistical significance. However, reaction time of threatening stimulus is significantly longer than neutral stimulus in the HDBR-8, indicating that HDBR may have an effect on the participants’ attention bias, and this effect is manifested as attention avoidance.